The Intersection of Digital Marketing and Sustainable Tourism: A Study on Tour de Siak’s Promotion and Environmental Awareness - Yesicha Chelsy; Nurjanah Nurjanah; Ismandianto Ismandianto; Suyanto Suyanto; Syaroni Umar; Nasution Belli; Putri Winda Ersa (E3S Web of Conferences)
This research examines various digital communication platforms, including social media and official websites related to the Tour de Siak activities as efforts in digital marketing and sustainable tourism. The event aligns with the Siak Green program, which emphasizes the importance of environmentally conscious tourism practices. This strategic synergy aims to position Siak as a premier sports tourism destination and to encourage community involvement in the Tour de Siak series. By using qualitative methodologies such as interviews and literature reviews primary data sourced from event organizers and participants, complemented by secondary sources from authoritative reports. Thematic analysis was employed to identify key trends. The results underscore the need for a comprehensive and sustainable marketing framework in promoting sports tourism globally. Ultimately, this research positions Tour de Siak as a quintessential of Siak’s tourism identity integrating digital marketing to support sustainable tourism goals. However, its promotion has not effectively educated tourists on environmental conservation althrough strong digital promotional efforts supported by government bodies and the Indonesian Cycling Federation (PB ISSI). The organizers still have the opportunity to enhance the message that is explicitly connected to the Siak Green initiative in line with potential digital trends and future environmental sustainability outreach strategies.